An Analysis of Must-be Attributes of Off-campus Student Housing Facilities and their Influence on Effective Learning: The Case of One University in South Africa - Anthony Kambi Masha; Nana Yaw Brenya Agyeman (E-Journal of Humanities, Arts and Social Sciences)
The high rate of university enrolment in South Africa has placed an immense burden on universities to provide accommodation services, with the institutions categorised as historically disadvantaged being the most severely affected. This phenomenon has led to the emergence and development of private off-campus student housing facilities as an alternative. To ensure that the student housing provided falls within the acceptable standards for effective learning and safety of the students, the Department of Higher Education and Training (DHET) has formulated a housing policy to inform developers of such housing standards. This study investigated whether the living conditions in student housing facilities (SHFs) comply with this Policy and how such conditions affect students’ academic performance, especially at historically disadvantaged higher education institutions (HEIs). A quantitative approach was used, using a closed-ended questionnaire to obtain data from respondents. The findings of this study revealed that the neighbourhood of off-campus housing facilities needed to be more satisfactory. However, the respondents found the social and physical dimensions of the houses and rooms somewhat acceptable, and they regarded the management of the facilities as commendable. The study concludes that the university should continue to work deliberately with developers so that they adhere strictly to the implementation of the student housing facilities policy to ensure effective learning and student safety. The study adds to existing research on student housing and its impact on effective learning.